Maternal sociodemographic characteristics, early pregnancy behaviours, and livebirth outcomes as congenital heart defects risk factors - Northern Ireland 2010-2014 - Hafi Saad (BMC, 2021)
Abstract Background Congenital Heart Defects (CHD) is the most commonly occurring congenital anomaly in Europe and a major paediatric health care concern. Investigations are needed to enable identification of CHD risk factors as studies have given conflicting results. This study aim was to identify maternal sociodemographic characteristics, behaviours, and birth outcomes as risk factors for CHD. This was a population based, data linkage cohort study using anonymised data from Northern Ireland (NI) covering the period 2010-2014. The study cohort composed of 94,067 live births with an outcome of 1162 cases of CHD using the International Statistical Classification of Diseases and Related Health Problems (ICD)-10 codes and based on the European Surveillance of Congenital Anomalies (EUROCAT) grouping system for CHD. CHD cases were obtained from the HeartSuite database (HSD) at the Royal Belfast Hospital for Sick Children (RBHSC), maternal data were extracted from the Northern Ireland Maternity System (NIMATS), and medication data were extracted from the Enhanced Prescribing Database (EPD). STATA version 14 was used for the statistical analysis in this study, Odds Ratio (OR), 95% Confident intervals (CI), P value, and logistic regression were used in the analysis. Ethical approval was granted from the National Health Service (NHS) Research Ethics Committee. Result In this study, a number of potential risk factors were assessed for statistically significant association with CHD, however only certain risk factors demonstrated a statistically significant association with CHD which included: gestational age at first booking (AOR = 1.21; 95% CI = 1.04-1.41; P < 0.05), family history of CHD or congenital abnormalities and syndromes (AOR = 4.14; 95% CI = 2.47-6.96; P < 0.05), woman’s smoking in pregnancy (AOR = 1.22; 95% CI = 1.04-1.43; P < 0.05), preterm birth (AOR = 3.01; 95% CI = 2.44-3.01; P < 0.05), multiple births (AOR = 1.89; 95% CI = 1.58-2.60; P < 0.05), history of abortion (AOR = 1.12; 95% CI = 1.03-1.28; P < 0.05), small for gestational age (SGA) (AOR = 1.44; 95% CI = 1.22-1.78; P < 0.05), and low birth weight (LBW) (AOR = 3.10; 95% CI = 2.22-3.55; P < 0.05). Prescriptions and redemptions of antidiabetic (AOR = 2.68; 95% CI = 1.85-3.98; P < 0.05), antiepileptic (AOR = 1.77; 95% CI = 1.10-2.81; P < 0.05), and dihydrofolate reductase inhibitors (DHFRI) (AOR = 2.13; 95% CI = 1.17-5.85; P < 0.05) in early pregnancy also showed evidence of statistically significant association with CHD. Conclusion The results of this study suggested that there are certain maternal sociodemographic characteristics, behaviours and birth outcomes that are statistically significantly associated with higher risk of CHD. Appropriate prevention policy to target groups with higher risk for CHD may help to reduce CHD prevalence. These results are important for policy makers, obstetricians, cardiologists, paediatricians, midwives and the public.